1998
DOI: 10.1016/s0893-133x(97)00131-0
|View full text |Cite
|
Sign up to set email alerts
|

D2-Like Dopamine Receptor Mediation of Social-Emotional Reactivity in a Mouse Model of Anxiety: Strain and Experience Effects

Abstract: We examined the effects of the D2-like dopamine receptor agonist quinpirole on social-emotional reactivity in two inbred mouse strains. An important objective of this study was to determine whether these effects could be modulated by differential housing conditions (i.e., isolation versus group housing). Moreover, as motor activity is an important control for the assessment of drug effects on emotional behavior, the effects of quinpirole were tested in two inbred mouse strains (A/J and C57BL/6J) low and high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…Oseltamivir is a representative neuraminidase inhibitor. Slip-down behavior in mice is induced by a comparatively low-dose of the dopamine D2 receptor agonist, PPHT (17), and that the representative dopamine D2 receptor agonists morphine and quinpirole induce jump-down behavior in mice (6,10). In addition, we noticed that mouse jump-down behavior appeared by increased doses of PPHT during previous experiment.…”
mentioning
confidence: 57%
“…Oseltamivir is a representative neuraminidase inhibitor. Slip-down behavior in mice is induced by a comparatively low-dose of the dopamine D2 receptor agonist, PPHT (17), and that the representative dopamine D2 receptor agonists morphine and quinpirole induce jump-down behavior in mice (6,10). In addition, we noticed that mouse jump-down behavior appeared by increased doses of PPHT during previous experiment.…”
mentioning
confidence: 57%
“…However, to investigate hypotheses about genes underlying autism, and to evaluate potential treatments, the field needs good behavioral tasks relevant to at least a subset of the more amenable symptoms of autism. We began with two core symptoms, aberrant social interaction and resistance to change in routine, because the natural repertoire of mice includes high levels of social interaction [46,85,116,117] and some examples of perseveration [53,54,99]. Our three-chambered automated social approach task was based on existing social tasks for rodents [17,42,46,69].…”
Section: Discussionmentioning
confidence: 99%
“…Research was conducted not only in these selectively bred mice (e.g., Gariépy, Gendreau, Mailman, Tancer, & Lewis, 1995;Gariépy, Gendreau, Cairns, & Lewis, 1998) but also in other strains of mice in order to assess the generality of our findings (e.g., Gendreau, Gariépy, Petitto, & Lewis, 1997a;Gendreau, Petitto, Gariépy, & Lewis, 1998;Gendreau, Petitto, Petrova, Gariépy, & Lewis, 2000). Briefly, our findings indicated that dopamine played an important role in the mediation of specific forms of social reactivity induced by prolonged social deprivation and suggested that D1-like and D2-like dopamine receptors were differentially involved in the expression of this reactivity.…”
Section: Paul L Gendreau and Mark H Lewismentioning
confidence: 72%